Artefactual 25-OH vitamin D concentration in multiple myeloma. (November 2017) - Ong, Michal WS; Salota, Rashim; Reeman, Tracy; Lapsley, Marta; Jones, Lydia
The most commonly used techniques to measure vitamin D are automated immunoassays which are known to be affected by interferences, especially from immunoglobulins present in the patient's serum. We present a case of a patient with myeloma in whom interference with the vitamin D assay was identified. An 83-year-old female, known to have IgG myeloma, was found to have a high concentration of 25-OH vitamin D on a routine test without any signs of vitamin D toxicity. She was not taking vitamin D supplements or any other multivitamin preparation and had minimal sun exposure. The initial and subsequent samples run by the ARCHITECT 25-OH vitamin D assay (chemiluminescent microparticle immunoassay technology, Abbott Laboratories, Abbott Park, IL) showed a high concentration of 25-OH vitamin D of 281 nmol/L and 327 nmol/L, respectively. Further fresh samples taken for 25-OH vitamin D and analysed by liquid chromatography-mass spectrometry (LC-MS/MS) and ARCHITECT analysis showed results of 49 nmol/L and 289 nmol/L, respectively. Our patient had high concentrations of circulating IgG paraproteins and had a long history of rheumatoid arthritis; paraproteins and rheumatoid factor may interfere in the assay. In conclusion, we report a case of a patient with IgG myeloma and rheumatoid arthritis with high concentrations of 25-OH vitamin D detected by the Abbott ARCHITECT, but not by a reference method (LC-MS/MS). The most likely cause of the discordant results is interference in the immunoassay by the paraprotein but interference from rheumatoid factor remains a possibility.